2019
DOI: 10.17541/optimum.531561
|View full text |Cite
|
Sign up to set email alerts
|

Price Volatility Spillover in Ship Demolition Markets

Abstract: World ship demolition activities are mainly carried out in Bangladesh, China, India, Turkey and Pakistan. Conducting in so few countries leads to a high level of competition among countries, as well as being influenced by each other's prices. So, there is no natural situation for each other to follow their prices, and this can be reflected as a flow of information to the variances of the prices. When this information flow exists, volatility spreads can be observed between the prices. In this context, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In addition, since demolition areas in the world are limited, the prices may be affected by each other. In another study, based on this research question, researchers tested the volatility spillover between demolition prices in these five countries (Açık and Başer, 2019). As a result of the analysis, it was found that there are volatility spillovers from Turkish demolition prices to almost all other countries' demolition prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, since demolition areas in the world are limited, the prices may be affected by each other. In another study, based on this research question, researchers tested the volatility spillover between demolition prices in these five countries (Açık and Başer, 2019). As a result of the analysis, it was found that there are volatility spillovers from Turkish demolition prices to almost all other countries' demolition prices.…”
Section: Literature Reviewmentioning
confidence: 99%